2006
DOI: 10.1021/jm0512600
|View full text |Cite
|
Sign up to set email alerts
|

Carbonic Anhydrase Inhibitors:  DNA Cloning and Inhibition Studies of the α-Carbonic Anhydrase from Helicobacter pylori, A New Target for Developing Sulfonamide and Sulfamate Gastric Drugs

Abstract: We have cloned and sequenced Helicobacter pylori alpha-class carbonic anhydrase (hpCA) from patients with different gastric mucosal lesions, including gastritis (n=15), ulcer (n=6), and cancer (n=16). Although several polymorphisms were newly identified such as 12Ala, 13Thr, 16Ile, and 168Phe, there was no significant relevance of any polymorphism with gastric mucosal lesion types. A library of sulfonamides/sulfamates has been investigated for the inhibition of hpCA, whereas new derivatives have been obtained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
105
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(106 citation statements)
references
References 56 publications
1
105
0
Order By: Relevance
“…As with CAs from other species, Hp CA is inhibited by sulfonamides, particularly by the anti-glaucoma drug acetazolamide (2-acetylamido-1,3,4-thiadiazole-5-sulfonamide; Chirica et al, 2002;Nishimori et al, 2006). Previous studies have shown that treating H. pylori with CA inhibitors drastically reduces the ability of the bacteria to survive within an acid environment, suggesting that CAs are essential for colonization of the stomach and duodenum Bury-Moné et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…As with CAs from other species, Hp CA is inhibited by sulfonamides, particularly by the anti-glaucoma drug acetazolamide (2-acetylamido-1,3,4-thiadiazole-5-sulfonamide; Chirica et al, 2002;Nishimori et al, 2006). Previous studies have shown that treating H. pylori with CA inhibitors drastically reduces the ability of the bacteria to survive within an acid environment, suggesting that CAs are essential for colonization of the stomach and duodenum Bury-Moné et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Other uses being explored include treatment of osteoporosis and as a diagnostic tool in magnetic resonance imaging (MRI) and photon emission tomography (PET) (25). Furthermore, other R-class CA isozymes that may be therapeutically targeted by CA inhibitors are found in the prokaryotic mammalian pathogens Neisseria gonorrheae, (28)(29)(30) Helicobacter pylori (31)(32)(33), and the eukaryotic malarial parasite Plasmodium falciparum (34)(35)(36). Known R-CA inhibitors include various anions, imidazole, phenol, hydroxyurea, carboxylates, organic phosphates and phosphonates, and various sulfonamide compounds (R-C-SO 2 NH 2 ) (4,11,25).…”
mentioning
confidence: 99%
“…This pathogenic bacterium lives in the highly acidic environment of the stomach (pH = 2-3). Its genome encodes three CAs: one α-, one β-, and one γ-CA, respectively [66][67][68][69][70]. The α-CA was shown to possess a periplasmic localization, the β-CA has been found in the cytoplasm, whereas no information is available on the expression/localization of the H. pylori γ-CA.…”
Section: Helicobacter Pylorimentioning
confidence: 99%
“…[103,104] Sulfanilamide, orthanilamide, some of their derivatives, and indisulam showed better activity (K(I)s in the range of 310-562 nM), whereas most of the clinically used CA inhibitors, such as methazolamide, ethoxzolamide, dichlorophenamide, brinzolamide, topiramate, zonisamide, etc., acted as medium potency hpCA inhibitors (K(I)s in the range of 124-287 nM) [70] .Some potent hpCA inhibitors were detected too (K(I)s in the range of 20-96 nM) such as acetazolamide, 4-amino-6-chloro-1,3-benzenedisulfonamide, 4-sulfanilyl-aminoethylbenzenesulfonamide, and 4-(2-amino-pyrimidin-4-yl)-benzenesulfonamide [70] .…”
Section: Hpαcamentioning
confidence: 99%